2019
DOI: 10.1038/s41374-019-0191-3
|View full text |Cite
|
Sign up to set email alerts
|

Polydatin mediates Parkin-dependent mitophagy and protects against mitochondria-dependent apoptosis in acute respiratory distress syndrome

Abstract: Mitophagy removes dysfunctional mitochondria and is known to play an important role in the pathogenesis of several diseases; however, the role of mitophagy in acute respiratory distress syndrome (ARDS) remains poorly understood. While we have previously demonstrated that polydatin (PD) improves lipopolysaccharide (LPS)-induced ARDS, the specific mechanism remains unclear. In present study, we aimed to determine whether PD activates Parkin-dependent mitophagy to protect against LPS-induced mitochondria-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 31 publications
2
36
0
Order By: Relevance
“…Additionally, the findings indicate that Parkin is involved in the mechanism underlying PD-mediated mitophagy. These findings are in agreement with those of our previous study, in which we reported that PD activates Parkin-mediated mitophagy in acute lung injury [18].…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Additionally, the findings indicate that Parkin is involved in the mechanism underlying PD-mediated mitophagy. These findings are in agreement with those of our previous study, in which we reported that PD activates Parkin-mediated mitophagy in acute lung injury [18].…”
Section: Discussionsupporting
confidence: 94%
“…Our previous study demonstrated that polydatin (PD) attenuates MD and inflammation in a rat model of SI-AKI [1], but the underlying pathways were not investigated. We have also demonstrated in a previous study that PD mediates Parkin-dependent mitophagy and protects against acute respiratory distress syndrome [18]. Based on our previous findings and those of other studies, in the present study, we hypothesized that Parkinmediated mitophagy plays a role in the protective effects of PD against MD and NLRP3 activation in SI-AKI and established a mouse model of sepsis.…”
supporting
confidence: 83%
See 3 more Smart Citations